Experiences and Coping Strategies among Families of Patients With Schizophrenia in Accra - Aryeequaye, R. (University of Ghana, 2016)
A case study research design was used to investigate caregivers burden and coping among families of patients with schizophrenia in Accra. A convenient sampling technique was used to sample one hundred (100) respondents. A set of questionnaires (Zarit Burden Interview scale and COPE Inventory) was used to gather data. The Statistical Package for Social Sciences (SPSS) was used for data analysis. Results indicated that no significant difference exists between the level of burden experienced by older caregivers and younger caregivers of schizophrenia patients. It was further revealed that no significant difference exist between the level of burden experienced by male and female caregivers of schizophrenia patients. Meanwhile, less educated caregivers report higher level of burden than well-educated caregivers. In addition, a significant difference exists between the way less educated and well educated caregivers of schizophrenia patients cope. It was finally revealed that a weak relationship exists between the burden faced by caregivers of schizophrenia patients and the way they cope. It was therefore concluded that demographic factors such as the age and gender had no effect on the level of burden experienced by caregivers of schizophrenia patients. Meanwhile, caregivers’ level of education significantly influenced the way they cope with the burden they experience. Generally, the level of burden faced by caregivers had little influence or effect on the ways of coping.
Thesis (MPhil.)
Keywords: Patients; Schizophrenia; caregivers; Ghana